ANALISIS FAKTOR ENGAGEMENT KARYAWAN GENERASI MILENIAL PADA PERUSAHAAN BERBASIS EKONOMI KREATIF - Sayadi Fahreza; Lindawati Kartika; Andita Sayekti (Jurnal Manajemen Indonesia, 2019)
The aims of this study were to analyse primary engagement driver of millennial generation employees on creative economy-based enterprise, to analyse engagement factors of millennial employees and formulate strategies for improving engagement in accordance with the characteristics of millenial generation employees. Data used in this study were primary data that collected from questionaire and secondary data from BPS, Bekraf and Aon Hewitt. The method used in this research were descriptive analysis, factor analysis and tree diagram model. The results of the study show that work life balance was primary engagement driver of millennial employee according to millennial perspective, autonomy and career opportunity were primary engagement driver according to experts perspective. Organization, compensation and benefit, the work, team work, pride, and performance were six engagement factors of millennial employees on creative economy enterprise. Tree diagram was presented to improve engagement of millennial employees on creative econonomy enterprise by Co-Auto Balance Gamification formula. Keywords—Creative economy; Engagement driver; Millennial. Tujuan dari penelitian ini adalah menganalisis engagement driver utama karyawan Generasi Milenial pada perusahaan berbasis ekonomi kreatif, menganalisis faktor-faktor engagement karyawan Generasi Milenial yang bekerja pada perusahaan berbasis ekonomi kreatif dan merumuskan strategi peningkatan engagement yang sesuai dengan karakteristik karyawan Generasi Milenial. Data yang digunakan dalam penelitian ini adalah data primer yang diperoleh melalui kuesioner dan data sekunder dari BPS, Bekraf dan Aon Hewitt. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif, analisis faktor dan model diagram pohon. Hasil penelitian menunjukkan bahwa work life balance adalah engagement driver utama menurut persepsi karyawan Generasi Milenial, autonomy dan career opportunity adalah engagement driver utama menurut persepsi pakar. Analisis faktor membentuk enam faktor engagement, yaitu organization, compensation and benefit, the work, team work, pride, dan performance. Model peningkatan engagement karyawan Generasi Milenial disajikan dalam diagram pohon dengan formula Co-Auto Balance Gamification. Kata kunci— Ekonomi kreatif; Engagement driver; Milenial.